Regulation of stanniocalcin secretion by calcium and PTHrP in Gilthead Seabream (Sparus aurata) - Ruiz-Jarabo, I. (2022)
Calcium balance is of paramount importance for vertebrates. In fish, the endocrine modulators of calcium homeostasis include the stanniocalcin (STC), and some members of the parathyroid hormone (PTH) family, such as the PTH-related protein (PTHrP), acting as antagonists. STC is ubiquitously expressed in higher vertebrates. In turn, bony fish exhibit specific STC-producing glands named the corpuscles of Stannius (CS). Previous studies pointed to a calcium-sensing receptor (CaSR) involvement in the secretion of STC, but little is known of the involvement of other putative regulators. The CS provides a unique model to deepen the study of STC secretion. We developed an ex vivo assay to culture CS of fish and a competitive ELISA method to measure STC concentrations. As expected, STC released from the CS responds to CaSR stimulation by calcium, calcimimetics, and calcilytic drugs. Moreover, we uncover the presence (by PCR) of two PTHrP receptors in the CS, e.g., PTH1R and PTH3R. Thus, ex vivo incubations revealed a dose-response inhibition of STC secretion in response to PTHrP at basal Ca2+ concentrations. This inhibition is achieved through specific and reversible second messenger pathways (transmembrane adenylyl cyclases and phospholipase C), as the use of specific inhibitors highlights. Together, these results provide evidence for endocrine modulation between two antagonist hormones, STC and PTHrP.